Medical accidents: A Socratic resolution?. Issue 2 (April 2020) - Feeny, Charles; Baker, Gus; Irving, Sam
Whilst medical accidents and adverse events clearly have to be the subject of response and redress for individuals who have suffered injury, the current approach to such accidents and events has developed in a piecemeal way. We argue that the various processes involved in such response and redress are outmoded and there is a lack of a clear overview, in particular in terms of promoting better clinical management and less psychological impact on the victim. The current effect of clinical negligence litigation produces adverse outcomes in terms of a patient's safety and the psychological wellbeing of victims. The time has come for an overall approach to be considered, which we suggest should be holistic and which would result in positive outcomes for the NHS and its patients.